Piling work construction / Muhammad Aiman Nasrullah Ahmad Ritzman - Ahmad Ritzman, Muhammad Aiman Nasrullah (Universiti Teknologi MARA, Perak, 2022)
Piling is a very important for a high rise building, therefore this report was conducted for the piling work construction that was held for additional block for Hospital Jerantut. The objective of this report is to learn about how the piling work construction work for a building and to know the progress to complete the piling work. To illustrate the function of piling construction as an important aspect to transferring building loads to under the surface and do all the procedure for piling work carefully. By doing all the procedure carefully, the deeper insertion of these parts provides a more stable foundation for the construction project and can avoid anything bad happen for the building.